Performance, meat quality, profitability, and greenhouse gas emissions of suckler bulls from pasture-based compared to an indoor high-concentrate weanling-to-beef finishing system. (April 2022) - McGee, M.; Lenehan, C.; Crosson, P.; O'Riordan, E.G.; Kelly, A.K.; Moran, L.; Moloney, A.P.
Abstract: CONTEXT: Demand for environmentally sustainable produced beef, especially 'grass-fed', is rising. Bull-beef production is a desirable alternative to steers due to large inherent growth and feed efficiency advantages. Compared to conventional indoor high-concentrate diets, pasture-finishing of bulls is low-cost, but carcass fat cover may not meet market requirements. OBJECTIVE: We evaluated the performance, meat quality, profitability, greenhouse gas (GHG) emissions, and human-edible protein (HEP) efficiency of pasture-based purchased suckler bull 'weanling'-to-beef finishing systems compared to an indoor high-concentrate system. METHODS: Suckler bulls, initially offered grass silage and supplementary concentrates during a 'backgrounding' phase, were assigned to one of four finishing systems: grazed grass with three levels of barley-based concentrate, 0 (G-0), 0.25 (G-25), and 0.50 (G-50) of predicted dietary dry matter intake, or ad libitum concentrates and grass silage (ALC). The experimental data generated were used to parameterise a whole-farm systems model and the output, profitability and GHG emissions of 'purchased weanling'-to-beef finishing systems were evaluated. RESULTS AND CONCLUSIONS: Total daily dry matter intake was highest for ALC and lowest for G-0. Carcasses from ALC were heavier (406 kg) than all grazing systems; G-50 was heavier (387 kg) than G-25 and G-0 (367 kg). Carcass fat score was higher for ALC (8.3, scale 1–15) than the grazing systems, which were similar (5.0–5.6). Meat eating quality did not differ between systems. Although carcass output per hectare increased by 50% for G-50 and almost-doubled for ALC compared to G-0, gross and net margins were similar for G-0 and G-50, and considerably less for ALC. The GHG emission per animal were lowest for G0 and highest for G50; however, when expressed relative to live-, carcass-, and especially meat weight, emission intensities (kg CO2 eq) were lowest for ALC (5.4, 14.9, and 12.2, respectively) and highest for G-0 and G-25 ( 9.6, 19.4, and 20.8, respectively). The HEP efficiency ratio was highest for G-0 (0.67) and lowest for ALC (0.21). Compared to a high-concentrate indoor bull finishing system, temperate pasture-based systems had lighter, 'under-finished' carcasses but similar meat eating quality, were more profitable, had superior HEP efficiency, but greater GHG emissions when expressed relative to live-, carcass-, and meat weight gain. SIGNIFICANCE: Although carcasses were 'under-finished' for the grazing systems compared to the high-concentrate indoor system, meat eating quality was similar, implying that, potentially, there is greater scope for beef producers to operate relatively more profitable pasture-based bull-beef finishing. In view of the inverse relationships between profitability, HEP efficiency, and GHG emissions per unit of product among different suckler weanling-to-beef finishing systems, consideration of unavoidable trade-offs is necessary from a beef production, policy and future-research perspective. Graphical ABSTRACT: Unlabelled Image Highlights: Demand for environmentally sustainable produced beef, especially 'grass-fed', is rising. Performance, meat quality, profitability, greenhouse gas emissions, and human-edible protein efficiency of contrasting bull systems was evaluated. Pasture-based systems had similar meat eating quality, greater profitability and superior human-edible protein efficiency than concentrate-based. Conversely, pasture-based systems had greater GHG emissions when expressed relative to live-, carcass-, and meat weight gain than concentrate-based. Inverse relationships between system profitability, human-edible protein efficiency, and greenhouse gas emissions implies inevitable trade-offs.